The adjuvant effect of polymuramil, a NOD1 and NOD2 agonist, differs when immunizing mice of different inbred lines with nonstructural hepatitis C virus (Flaviviridae: Hepacivirus)proteins and is synergistically enhanced in combination with pyrogenalum, a TLR4 agonist - Ekaterina I. Lesnova; Olga V. Masalova; Kristina Yu. Permyakova; Natalia A. Demidova; Vladimir T. Valuev-Elliston; Alexandr V. Ivanov; Alla A. Kushch (Вопросы вирусологии, 2023)
Introduction. Hepatitis C is a liver disease with high chronicity, the cause of cirrhosis and hepatocarcinoma. The main obstacle to controlling hepatitis C is the lack of vaccines.